The world is watching - Crooks, Harold; Monro, Jun.; Raymont, Peter (Canada Investigative Production, 1988)
It presents the November 1987 revolution in Nicaragua.
VHS.
Narrator, Elizabeth Gray.
Keywords: Nicaragua -- History -- Revolution, 1987.; History